2009
DOI: 10.1016/j.rasd.2009.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Relationships among repetitive behaviors, sensory features, and executive functions in high functioning autism

Abstract: This study examined the relationship between repetitive behaviors and sensory processing issues in school-aged children with high functioning autism (HFA). Children with HFA (N = 61) were compared to healthy, typical controls (N = 64) to determine the relationship between these behavioral classes and to examine whether executive dysfunction explained any relationship between the variables. Particular types of repetitive behavior (i.e., stereotypy and compulsions) were related to sensory features in autism; how… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
111
2
6

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 160 publications
(126 citation statements)
references
References 27 publications
7
111
2
6
Order By: Relevance
“…In other words, symptoms of communication and social interactions will be intensified when deficiency of selective attention increases. The results of regression analysis also showed that selective attention can predict communication and stereotyped behaviors, which is consistent with the results obtained by other researchers (3,4,19).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In other words, symptoms of communication and social interactions will be intensified when deficiency of selective attention increases. The results of regression analysis also showed that selective attention can predict communication and stereotyped behaviors, which is consistent with the results obtained by other researchers (3,4,19).…”
Section: Discussionsupporting
confidence: 91%
“…Autism disorders refer to a spectrum of neuro-developmental disorders in early stages of development identified by impairments in social interactions, communication and daily functions (1,2). Repetitive actions, behaviors, and interests of children with autism are representative of deficit executive functions (3). Executive functions play an important role in socio-emotional functions (4), educational functions, use of working memory, problem solving, goal setting for doing tasks (5) and motor behaviors (6).…”
Section: Introductionmentioning
confidence: 99%
“…Studies investigating cognitive flexibility in natural settings by means of the Behavior Rating Inventory of Executive Function (BRIEF) have shown that people with ASD have problems with flexibility in daily life (Gioia, Isquith, Kenworthy, & Barton, 2002;Mackinlay, Charman, & Karmiloff-Smith, 2006). These flexibility deficits have also been related to the repetitive behaviors typical for ASD (Boyd et al, 2009). However, studies measuring cognitive flexibility in a clinical or research setting have yielded more inconsistent findings.…”
mentioning
confidence: 99%
“…Indeed, the most thorough meta-analysis to date found that sensory modulation issues consistently distinguish ASC and TD individuals across studies (Ben-Sasson et al, 2009). Sensory issues are largely separable not only from cognitive inflexibility (as argued above), but also from executive functioning (Boyd et al, 2009;Chen et al, 2009), and social interaction deficits (Watson et al, 2011), the latter observable as early as infancy (Baranek, 1999). Moreover, although the affected modalities can vary greatly between ASC individuals (perhaps explaining some of the ambivalence towards including sensory issues as a core symptom) there is some evidence that, within ASC individuals, severity of sensory modulation abnormalities highly correlates across sensory modalities (Kern et al, 2007).…”
Section: Two Additional Adi-r Factor Analyses Within the Restricted Amentioning
confidence: 99%